2019
DOI: 10.1590/1983-21252019v32n123rc
|View full text |Cite
|
Sign up to set email alerts
|

Soil Chemical Properties in Banana Crops Fertigated With Treated Wastewater

Abstract: Determining the effects of using wastewater as fertilizer on soil chemical properties allows a safe reuse of this effluent in agriculture. This study evaluated the effects of fertigation with tertiary treated wastewater (TTW) from the Janaúba sewage treatment plant on chemical properties of a Latosol (Oxisol) with banana crops of the Prata-Anã cultivar in the semiarid region of Brazil. A randomized complete block design with four replications was used to test four TTW rates (70%, 130%, 170%, and 200% of the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…A inundados do solo podem alterar o pH do solo (VOURLITIS et al, 2017). O pH adequando do solo resulta em redução na concentração de Al 3+ (ausência de mapa de Al 3+ devido o valor ser zero em toda a área) o que favorece a predominância de cátions de menor valência (K + , Ca 2+ , Mg 2+ ) no complexo de troca do solo, favorecendo uma melhor nutrição mineral (ALVES et al, 2019). Apesar de no presente estudo o pH do solo encontrar-se adequando, geralmente o pH do solo tende a diminuir com as inundações sazonais, devido em parte a lixiviação das bases e a decomposição mais lenta da matéria orgânica que poderá levar a maior liberação de ácidos orgânicos no solo, assim, contribuindo para sua acidificação (LACROIX et al, 2019;PONTING et al, 2021).…”
Section: Resultados E Discussõesunclassified
“…A inundados do solo podem alterar o pH do solo (VOURLITIS et al, 2017). O pH adequando do solo resulta em redução na concentração de Al 3+ (ausência de mapa de Al 3+ devido o valor ser zero em toda a área) o que favorece a predominância de cátions de menor valência (K + , Ca 2+ , Mg 2+ ) no complexo de troca do solo, favorecendo uma melhor nutrição mineral (ALVES et al, 2019). Apesar de no presente estudo o pH do solo encontrar-se adequando, geralmente o pH do solo tende a diminuir com as inundações sazonais, devido em parte a lixiviação das bases e a decomposição mais lenta da matéria orgânica que poderá levar a maior liberação de ácidos orgânicos no solo, assim, contribuindo para sua acidificação (LACROIX et al, 2019;PONTING et al, 2021).…”
Section: Resultados E Discussõesunclassified
“…The results showed lower spatial variability of K + among the depths analyzed (Figure 1), presenting similar values ranging from 0.06 to 0.56 cmolc dm -3 , classified as very low and low levels. Due to the fortnightly mineral fertilizations to be launched with potassium chloride and ammonia sulfate, according to the need of the crop; it is emphasized that banana requires high concentrations of K + and, in soils with <0.60 cmol c dm -3 , potassium fertilization is required to meet the crop demand (GERUM et al, 2019;ALVES et al, 2019). It was observed that the depth of 0.20-0.40 m presented a reduction which can be attributed to export by the fruits, agreeing with Alves et al (2019), where they concluded that, in an area cultivated with banana trees under irrigation with wastewater, the reduction of K + in the soil can be justified by the greater extraction of the crop due to increased productivity.…”
Section: Resultsmentioning
confidence: 99%
“…The pH increase decreased the Al 3+ concentrations, allowing lower valence cations (K + , Ca 2+ , Mg 2+ ) to dominate the exchange complex, thus improving the mineral nutrition of banana plants due to their high demand for cation nutrients (ALVES et al, 2019). Since the studied soil is sandy (Table 1), part of the limestone applied on the surface might have been reallocated to the subsurface, allowing greater pH uniformity in all areas and at all depths studied (Figure 2).…”
Section: Geoestatisticsmentioning
confidence: 99%
“…In addition, the rapid annual growth of banana demands signifi cant soil nutrient levels, with fertigation emerging as a viable tool to supply the nutrient demands of this crop. In this scenario, due to the possibility of using local and split fertilization in fertigation systems, soil fertility evaluation is essential to standardize producing areas and improve the quality of banana plantations (ALVES et al, 2019). Fertigation brings benefi ts such as applying adequate fertilizer levels, especially if the irrigation system adopts a mulch cover (XAVIER et al, 2020), resulting in higher plant heights, increased yield, and higher water, nitrogen, and potassiumuse effi ciency by banana plants (SOUZA et al, 2021).…”
Section: Introductionmentioning
confidence: 99%